Distributed control in testable high-level synthesis with low area and power overhead - Harmanani, Harmanani (2017)
This work presents a method for distributed test control in coordination with testable data path allocation in high-level synthesis. The method aims at creating distributed test controllers for synthesized data paths with the aim of minimizing area and power consumption. The distributed controllers are designed to be small and mounted next to their corresponding test kernels. Thus, every test kernel in the datapath has its own test controller in addition to a relatively small controller that synchronizes the distributed controllers. The system has been implemented using C++ and favorable results are reported.